The Relationship Between Production, Consumption, and Food Estate Budget on Soybean Imports in Indonesia - I Gde Ari Karisma; Ni Putu Wiwin Setyari (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
Carbon emission disclosure is increasingly important for companies in establishing legitimacy, enhancing stakeholder trust, and drawing public attention to sustainability issues. This study aims to examine how profitability, leverage, and company size affect carbon emission disclosure. The research is grounded in legitimacy theory and stakeholder theory, which provide the theoretical foundation for understanding corporate carbon disclosure behavior. The population of this study comprises energy companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. The sample was selected using non-probability purposive sampling, resulting in 113 observations. Data were analyzed using SPSS with multiple linear regression techniques. The results indicate that profitability and company size have a positive influence on carbon emission disclosure, while leverage does not have a significant effect. Theoretically, the findings support the notion that profitability and company size drive carbon disclosure, in line with legitimacy and stakeholder theories.